Black Phosphorous/Indium Selenide Photoconductive Detector for Visible and Near‐Infrared Light with High Sensitivity. Issue 12 (29th March 2019) - Cao, Rui; Wang, Hui‐De; Guo, Zhi‐Nan; Sang, David K.; Zhang, Li‐Yuan; Xiao, Quan‐Lan; Zhang, Yu‐Peng; Fan, Dian‐Yuan; Li, Jian‐Qing; Zhang, Han
Abstract: 2D materials offer tremendous opportunities for designing and investigating multifunctional high‐performance electronic and optoelectronic devices. In this contribution, a photogate vertical structure is devised by vertically stacking layered indium selenide (InSe) on top of layered black phosphorous (BP). The photodetector built with the vertical structure possesses a wide response range from 405 to 1550 nm, and the photodetector exhibits a relatively fast (≈22 ms) response and high responsivity of ≈53.80 A W −1 at λ = 655 nm and 43.11 A W −1 at λ = 1550 nm, respectively. Under visible‐light illumination (λ = 655 nm), the external quantum efficiency of the device can reach 1020%. By taking advantage of gate‐tunable modulation, the forward‐to‐reverse bias current ratio is as high as 10 3 . In addition, the environmental degradation of BP could be effectively suppressed by InSe capping. The high sensitivity, broad spectral response, and enhanced stability of the photodetector show that the photogate structure provides a new opportunity for broad spectral detection or imaging at room temperature by using 2D materials with a vertical structure. Abstract : In this contribution, a photogate vertical structure is devised by vertically stacking layered indium selenide (InSe) on top of layered black phosphorous (BP). The vertical structure photodetector possesses spectra response range from visible to near‐infrared, and the photodetector exhibits a relatively fast response and high responsivity. Furthermore, the environmental degradation of BP also can be inhibited by layered InSe capping.